1994
DOI: 10.1001/archpsyc.1994.03950090019003
|View full text |Cite
|
Sign up to set email alerts
|

Mood-Lowering Effect of Tryptophan Depletion

Abstract: Our data support the hypothesis that subjects with no prior depressive episodes but with a multigenerational family history of major affective disorder show a greater reduction in mood after tryptophan depletion. They are also consistent with theories that implicate deficient serotonergic function as one possible etiological factor in major depressive disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(61 citation statements)
references
References 50 publications
6
55
0
Order By: Relevance
“…Clarifying studies have found that increased susceptibility to mood effects occurs in healthy subjects at genetic risk for depression (27), in women (28) and in remitted subjects with major depressive disorder -whether receiving medication (29) or not receiving medication (30). The probability of TD-induced mood symptoms is highest in remitted patients with a major depressive disorder and in those who are treated with selective SSRIs (31).…”
Section: Tryptophan Depletion (Td) Studiesmentioning
confidence: 99%
“…Clarifying studies have found that increased susceptibility to mood effects occurs in healthy subjects at genetic risk for depression (27), in women (28) and in remitted subjects with major depressive disorder -whether receiving medication (29) or not receiving medication (30). The probability of TD-induced mood symptoms is highest in remitted patients with a major depressive disorder and in those who are treated with selective SSRIs (31).…”
Section: Tryptophan Depletion (Td) Studiesmentioning
confidence: 99%
“…The latter hypothesis for a causal role of 5-HT in MDD has often been dismissed over the years, because of a lack of consistency of observations on a decrease of 5-HT concentrations in post-mortem brain samples, and the fact that acute tryptophan depletion does not produce depression in healthy controls, tryptophan being the essential amino acid precursor of 5-HT [6]. Nevertheless, in unaffected individuals with a family history of depression, mild dysphoric symptoms can be triggered by this acute 5-HT-lowering challenge [7]. One can thus wonder whether a prolonged 5-HT lowering might not lead to MDD.…”
Section: Introductionmentioning
confidence: 99%
“…Second, ATD induces a transient reappearance of depressive symptoms in patients under treatment with antidepressants (13). Moreover, ATD also produces a mild lowering of mood in normal subjects with a family history of depression (14). It is therefore of interest to determine the degree of reduction in serotonin synthesis associated with changes in mood.…”
mentioning
confidence: 99%